OBTAINING CALCIUM BINDING MATERIALS BASED ON GYPSUM WASTE AND STUDYING THEIR PROPERTIES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This scientific article presents the results of research conducted on the production of calcium binders from gypsum waste generated at porcelain production enterprises operating in the Rishton district of Fergana region. The conversion of gypsum waste into a primary product by adding additives to the composition at different temperatures was determined. The hardening of samples heated at the same temperature and for different periods of time in different proportions under the influence of water was studied. The mechanical strength, compressive strength and water absorption of the obtained samples were determined relative to the standard. IR spectral analysis of the obtained samples was studied.